Македонија во книжевните дела на Лав VI и Константин VII: Историја и легенда (Filološke pripombe, 2019)
The analysis of the works of emperors Leo VI and Constantine Porfyrogenitus illustrate the tendency of representatives of the Macedonian dynasty in Byzantium for creating the impression that they are associated with the name Macedonia as well as with the Macedonian historical traditions. This ideology was generally created by Porfyrogenitus who, in his Vita Basilii, introduced the story about a direct relationship with Philip II and Alexander III the Macedon in the genealogy of his grandfather Basil I, apart from the ancient Armenian ancestry with the Arsacids,. To attach the Macedonian descent of the dynasty founded by Basil I, in his De thematibus Porfyrogenitus deliberately represented Macedonia in a wider geographical area, creating an impression that the administrative unit–theme with the same name Macedonia was an integral part in geographical as well as in historical connotation. The tendency for glorification of the dynasty with the Macedonian historical traditions resulted in its definite association with the name Macedonia and Macedonians, which became an essential part of the identity appellation and identification of the emperors of the Macedonian dynasty. This political ideology significantly impacted the perception of the Byzantine authors and their use of Macedonian terminology in elaborating the contemporary events related to Macedonia in the 9 th -12th century